Atrial Septal Defect with Paroxysmal Atrial Tachyarrhythmia in Middle Age Soldier Patient: A Case Report - Ford Ance E. Aritonang; Hasanah Mumpuni; Real Kusumanjaya Marsam; Lucia Kris Dinarti (Universitas Airlangga, 2023)
Highlights: 1. ASD closure is still recommendable in late middle-aged patients, especially one that is combined with arrhythmias management. 2. ASD closure after age 40 seems to not affect the frequency of arrhythmia development during follow up. - Background: Atrial septal defects (ASDs) are frequently asymptomatic and can remain undiagnosed until adulthood. Atrial tachyarrhythmias are not uncommon seen in patients with ASDs. Atrial fibrillation and atrial flutter are relatively rare in childhood, but become more prevalent with increasing age at time of repair or closure. Case Summary: The present case was an active duty 50-year-old male soldier, referred to the arrhythmia division of Gatot Soebroto Army Hospital with palpitations and physical intolerance. Holter examination and electrophysiology study revealed atrial tachyarrhythmias. Transesophageal echocardiography was performed before radiofrequency catheter ablation, and unexpectedly found left to right shunt ostium secundum ASD. Right heart catheterization confirmed left to right shunt ASD with high flow-low resistance. He then underwent paroxysmal atrial tachyarrhythmias catheter ablation, followed by percutaneous transcatheter ASD closure using occluder device without fluoroscopy within six months. Both the procedures went well without any complications. His symptoms had improved during follow up, although he had episode of rapid paroxysmal atrial fibrillation on holter evaluation six months later. Conclusion: We conclude that ASD closure is still recommendable even in late middle age patients combined with arrhythmias management.